Persistent Non-Compliance in Construction Contracts: Comparative Insights from Capital Expenditure Audit Findings (2024-2025) - Cahyo Sadewo Hutomo; Henryanto Wijaya (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
This study comparatively analyzes the determinants of non-compliance regarding physical volume shortages in capital expenditure construction contracts for Buildings/Structures and Roads/Networks/Irrigation for the 2024–2025 period in XYZ Regency. Employing a descriptive-comparative qualitative approach, this research integrates Agency Theory and the Theory of Planned Behavior (TPB) utilizing BPK RI audit reports (2025–2026) and SIPD-RI digital transaction logs. The results indicate that externally, contractors (agents) engage in adaptive moral hazard; Building project manipulations focus on spatial dimensions (hidden structure), whereas road projects exploit geographical distance (exposed structure). Internally, mitigation failures stem from officials' (principals') permissive attitude prioritizing formal handover documents (BAST) and curative recovery (STS), exacerbated by the end-of-year backloading effect in SIPD-RI that triggers control overload. This study recommends contract governance reconstruction through procurement scheduling reforms (early bidding), enhanced technical competence, and geospatial-based digital quality control.